PENDIDIKAN INKLUSIF PADA KURIKULUM MERDEKA - Victorria Yunus; Amrazi Zakso; Antonius Totok Priyadi; Agung Hartoyo (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
Education is a right for every child, including children with special needs. Inclusive education is an education that requires educational units to provide learning for children with special needs along with normal children. In this independent curriculum, inclusive education is being intensified again so that all children experience the same education. However, in reality, inclusive education has not been implemented well due to several factors, such as the misunderstanding of schools who think that inclusive education is only for Special Schools “Sekolah Luar Biasa” (SLB). The aim of the research is to describe the basis of regulations so that the importance of implementing inclusive education in regular schools is taken into consideration. This research is qualitative research with the type of library research. Data collection techniques use documentation techniques. The documents that are the data source are laws relating to inclusive education and supporting scientific journals regarding inclusive education. Research data shows that in Indonesia inclusive education was introduced in the 1980s. This inclusive education is guaranteed by law. The foundations for implementing inclusive education such as Law no. 4 of 1997, Law no. 23 of 2002 articles 48 and 49, Law no. 20 of 2003 article 5 paragraph 1, as well as the publication of a guidebook for implementing inclusive education in the independent curriculum by the Ministry of Education and Culture. So that schools must be able to implement inclusive education in regular schools in accordance with the mandate of the law.